If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + -3x = 0 Solving 7a + -3x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3x' to each side of the equation. 7a + -3x + 3x = 0 + 3x Combine like terms: -3x + 3x = 0 7a + 0 = 0 + 3x 7a = 0 + 3x Remove the zero: 7a = 3x Divide each side by '7'. a = 0.4285714286x Simplifying a = 0.4285714286x
| 8(t+2)-3(t-4)=-3(5y-7)-8 | | -1/9(x-27)+1/3(x+3)=x+11 | | y=-5/3x+7 | | 6/3 | | (y-9)-(y+1)= | | 15-0.75a=13-0.5a | | 6/8 | | 1/2-5/8x=7/8x+7/2 | | 330000=3x | | y=4-7x | | 2z-4(9-32)=62 | | 9(5)= | | 10=4-1x | | 6x^2-5x=2x+3 | | 125x^6+216g^3= | | -8=-2(c+1) | | 4r^2*4= | | 8x-5-3x=-15 | | 6x(2)-5x=2x | | X/7+4/7-x/5-3/5=4 | | 2x+1/2y=6 | | Y-160=-81/2(X-0) | | X+4/7-x-3/5=4 | | 1/6x=491/6 | | 30a=80+22a | | 4r^2*r= | | 6(x)=8x-3 | | 0=7/3x-7/2 | | 2/3(x)^2+7/3(x)=5 | | -16-10x=2(-7x+6) | | (x-7)*(x-6)= | | X-6=2x+12 |